RESPONSABILIDADE PENAL DA PESSOA JURÍDICA POR CRIMES AMBIENTAIS - Scherner, Ana Luiza; Schaefer, Marcus Vinícius; Da Silva, Thiago Dos Santos (Salão do Conhecimento, 2018)
Projeto de iniciação científica